Building future health and well-being of thriving toddlers and young children : - Abrams, Steven A.; Adolph, Karen Elizabeth; Au, Lauren E.; Barcelona, Jeanne M.; Bier, Dennis M.; Black, Maureen M.; Singhal, Atul; Hillman, Charles H. (Nestlé Nutrition Institute workshop series, 2020)
The early child period is considered the most important developmental phase throughout the lifespan. The 95th Nestlé Nutrition Institute Workshop explored in some detail the current scientific research, challenges, and opportunities of cementing a healthy foundation for life in toddlers and young children. The workshop brought together experts in the areas of health care, public health, and developmental science. The first session focused on the nutritional challenges in toddlers and young children across the globe, such as overweight and obesity. The theme of the second session elucidated the journey from infancy to toddlerhood and the role of nutrition in it, focusing social aspects. And finally, the third session aimed to explain the steps of motor skill development and the role of physical activities and nutrition in cognitive development and learning abilities of a child. The key issues offer valuable insights for health care providers, policy makers, and researchers on how appropriate nutrition, nurturing caregiving, and environment can influence the development and health of children up to 5 years of age.